2019
DOI: 10.1109/tcpmt.2019.2929017
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Material Heatsink Design Using Level-Set Topology Optimization

Abstract: In this article we apply a Level-set topological optimization algorithm to the design of multi-material heat sinks suitable for electronics thermal management. This approach is intended to exploit the potential of metal powder additive manufacturing technologies which enable fabrication of complex designs. The article details the state-of-the-art in topological optimization before defining a numerical framework for optimization of two-material and three-material based heatsink designs. The modelling framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Although one gene value of each design element is optimized in the single-material topology optimization, the design variables of multi-material topology optimization are twice the number of the single-material topology optimization (Sato et al , 2015; Jung and Min, 2019; Santhanakrishnan et al , 2019; Guo and Brown, 2019; Shah et al , 2021). Consequently, the solution space becomes more complex than that of single-material topology optimization.…”
Section: Optimization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one gene value of each design element is optimized in the single-material topology optimization, the design variables of multi-material topology optimization are twice the number of the single-material topology optimization (Sato et al , 2015; Jung and Min, 2019; Santhanakrishnan et al , 2019; Guo and Brown, 2019; Shah et al , 2021). Consequently, the solution space becomes more complex than that of single-material topology optimization.…”
Section: Optimization Methodsmentioning
confidence: 99%
“…In the present study, a novel multi-material topology optimization method is proposed to improve the performance of PM-SyRMs. In the conventional method, the distributions of the magnet, core and air materials are varied simultaneously (Sato et al , 2015; Jung and Min, 2019; Santhanakrishnan et al , 2019; Guo and Brown, 2019; Shah et al , 2021). Because design parameters, by which the material distribution of magnets, cores and air is expressed, are more than that of the single-material topology optimization, the solution space becomes more complex and it is difficult to obtain optimal solutions with better performance using the conventional multi-material topology optimization method.…”
Section: Introductionmentioning
confidence: 99%
“…Through this structure, both the magnet and reluctance torque can be utilized effectively; thus, high torque can be obtained with a small magnet. To apply the topology optimization method to hybrid-type motors, multi-material topology optimization is required [21][22][23][24]. In [21], the magnet, flux barrier, and core shape of a PM motor were represented by multiple shape functions.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Syed-Khaja et al [ 14 ] used PBF to fabricate a heat sink design that showed key enabling advantages such as the reduction in volume, weight, and chip temperatures. To date, several other studies have emerged regarding heat sinks produced by additive manufacturing [ 5 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%